ANALISIS HUKUM PENERAPAN SANKSI PIDANA TERHADAP PELAYARAN KAPAL YANG TIDAK LAIK LAUT DI WILAYAH PELABUHAN GORONTALO - Darmawati Darmawati (AkMen JURNAL ILMIAH, 2016)
The purpose of this research is to investigate the application of sanctions against the manning of merchant ships that do not meet the qualifications and competence as well as to know which of the factors that affect the application of sanctions against the manning of merchant ships that do not meet the qualifications and competence in the port area Gorontalo. Metodh used is empirical legal research / sociological, the law conceived as an institution which in real terms are associated with other social variables. Sociological research using secondary data as the data initially, followed by a primary data or field researce. Conclusions from the findings that the imposition of sanctions against the manning of merchant ships that do not meet the qualifications and competence in the port area Gorontalo because there is not yet maximal application of criminal sanctions as stipulated in Article 310 of Law No. 17 of 2008 on the voyage. Sanctions are applied only to the extent the administrative sanctions and seizure of documents of the ship. The factors that hinder the application of criminal sanctions are investigators who do not have a certificate or has not even been sworn in completing education and training. Investigators who have sworn will have an impact on the validity of a legal process that is handled. Similarly, the leadership policy that does not emphasize the investigation of criminal offenses manning of merchant ships that do not meet the qualifications and competence due to the lack of budget allocation investigations, the lack of a fleet of patrol boats, patrol boats which are old and greatly decreased ability not to mention the legality of the investigators. So if there are violations of the sanctions was only limited to administrative sanctions.